The Belhar Confession in its historical context - Plaatjies-van Huffel, Mary-Anne (Nederduitse Gereformeerde Teologiese Tydskrif, 2014)
In this article I work with the presupposition that the time has arrived that the Belhar Confession should be detached from being a document utilized for advocacy perusal only. The Belhar Confession should rather be interrogated as a historical document in the true sense of the word. This will be helpful in construing the Belhar Confession as a discursive instrument in the discourse on social justice issues both local and global. The article is divided into four parts. In the first part the focus is largely on the socio political context of SA during 1960-1990. In the second part the influence of the ecumenical movement on the discourse on social justice is being attended to. Thirdly I attend to the drafting of the Belhar Confession and lastly attention will be given to the reception of the Belhar Confession (1982-1990).